A Computationally Efficient Numerical Simulation for Generating Atmospheric Optical Scintillations - Jurado-Navas, Antonio; Garrido-Balsells, José María; Castillo-Vázquez, Miguel; Puerta-Notario, Antonio (IntechOpen, 2011)
None